PERSPEKTIF HUKUM EKONOMI SYARIAH TERKAIT SABUNG AYAM GUNA MENINGKATKAN HARGA JUAL - Sri Mulyani (Fakultas Hukum Universitas Muhammadiyah Palu, 2023)
ABSTRACT The purpose of this study is to examine the views of sharia economic law regarding the quality test of chickens by means of fighting in order to increase the selling price. This study uses a sociological legal research method with a qualitative approach. The results of this study indicate that the cockfighting conducted at the Ambarawa Animal Market does not use a gambling system but in order to test the quality or strength of the chickens in order to increase the selling price of the chickens which if the chicken wins or is able to survive until the end of the cockfighting session then the chicken will have a price. selling high, on the contrary with the losing chicken, the chicken will experience a decrease in the selling price, thus it is still contrary to Sharia Economic Law even though basically it does not use a gambling system, but from this activity there is one party who is harmed which this is not in accordance with the provisions of buying and selling in Islamic law.